Carbonation Characteristics of Alkali-Activated Blast-Furnace Slag Mortar. (7th August 2014) - Song, Keum-Il; Song, Jin-Kyu; Lee, Bang Yeon; Yang, Keun-Hyeok
Abstract : Alkali-activated ground granulated blast-slag (AAS) is the most obvious alternative material for ordinary Portland cement (OPC). However, to use it as a structural material requires the assessment and verification of its durability. The most important factor for a durability evaluation is the degree of carbonation resistance, and AAS is known to show lower performance than OPC. A series of experiments was conducted with a view to investigate the carbonation characteristics of AAS binder. As a consequence, it was found that the major hydration product of AAS was calcium silicate hydrate (CSH), with almost no portlandite, unlike the products of OPC. After carbonation, the CSH of AAS turned into amorphous silica gel which was most likely why the compressive strength of AAS became weaker after carbonation. An increase of the activator dosage leads AAS to react more quickly and produce more CSH, increasing the compaction, compressive strength, and carbonation resistance of the microstructure.